Histological Changes on Liver Glycogen Storage in Mice () Caused by Unbalanced Diets - Esma Ulusoy; Banu Eren (SAGE Publishing, 2008)
Weight-losing diets have appealed to people who want to lose weight in the short-term. They usually apply high-protein (HP) diets (like Atkin's, Stillman's, Scarsdale) which they practice for 2 weeks or so. Unfortunately, these people who have rapid weight loss return to their old habits and quickly regain the weight lost. We have shown in previous work that actually these weight losses have been associated with body fluids, protein and glycogen storage. In our study, we examined the effect of unbalanced diet--related to an HP diet- on liver glycogen storage. For this study 40 Swiss albino mice consisting of two groups were used. The first group (HPSD) was fed with 25% HP for fifteen days and then were fed standard meals for the remaining 15 days; the other group was fed with standard meals throughout. The two groups were fed their respective diets for 30 days. At the end of 15th, 20th, 25th and 30th days 5 from each group were killed with cervical dislocation. The livers were removed perfused and then fixated. There were major differences in weight between the first and the fifteenth days. We detected remarkable increase in the weight gain of mice in the remaining 15 days. Glycogen storage was significantly reduced in HPSD (15) stained with PAS. In the others 20th, 25th and 30th days abnormally dense glycogen deposits were observed. Vacuoles in the hepatocyte cytoplasm, brownish deposits within hepatocytes, wide sinusoids, macrovesiculler steatosis structures and hydropic degeneration were observed in PAS and H&E stained HPSD group. As a result for the HPSD group a significant decrement in glycogen storage at the 15th day and also an accumulation of excessive amounts of glycogen deposits in mice liver was observed in the normal feeding phase.